P82 Episodic viral wheeze and multitrigger wheeze: are they really different phenotypes?. (2nd December 2011) - Livingstone, E; Noble, G; Walsh, G; Turner, S
Abstract : Introduction: Episodic viral wheeze (EVW) and multitrigger wheeze (MTW) are thought to be distinct recurrent wheezing phenotypes in preschool children. Here we tested the hypothesis that there are detectable physiological differences between children with EVW and MTW. Methods: Preschool children with and without a history of recurrent wheeze were recruited, those with symptoms were categorised as EVW or MTW. In a single assessment, the following were completed: questionnaire, respiratory resistance (Rint), bronchodilator response, nasal nitric oxide and skin prick reactivity. Exhaled breath condensate was collected and analysed for interleukin (IL) −10 concentration. A respiratory questionnaire was completed after 12 months. Results: There were 69 children recruited, mean age 3.8 years (range 2.1–5.3), of whom 34 had EVW, 19 had MTW and 16 were controls. Skin prick reactivity was determined in 57, Rint in 55, bronchodilator response in 43, nasal NO in 42, exhaled breath condensate in 24 and follow-up was achieved in 53 children. Compared with MTW, children with EVW had increased Rint (mean difference 0.21 kPa.s/L [95% CI 0.06 to 0.36]). Children with MTW were 4.0 times more likely [95% CI 1.1 to 14.7] to be atopic compared with those with EVW. Compared with controls, children with EVW and MTW had reduced IL-10 concentration in exhaled breath condensate (mean difference 1.35 pg/ml [95% CI 1.02 to 1.87]. After 12 months, wheeze had apparently resolved in 27% (12/44) children and of the 30 with ongoing wheeze, 27% (3/11) with MTW were categorised as EVW and 52% (10/19) with EVW had developed MTW. Conclusions: There are differences in lung function and atopy between children with EVW and MTW but with considerable overlap in values. The two phenotypes are not necessarily stable over time suggesting they are towards opposite ends of the same spectrum rather than different conditions.